The Role of Vocational Education in Indonesia's Economic Development - Ichwanto, Muhammad Aris; Hidayat, Wahyu Nur; Sutikno, Tri Atmadji; Indraswari, Martha Devi; Asfani, Khoirudin (Teknologi dan Kejuruan: Jurnal Teknologi, Kejuruan, dan Pengajarannya, 2020)
Education, including vocational education, has an essential role in the development of complete human beings and the development of the Indonesian people as a whole. Human development must be done intact, which includes the development of thinking power, emotional intelligence, physical power, and mastery of science, technology, art and sport. Besides, human development is also expected to produce human capable of and able to play an active role in building the entire Indonesian society. The success or failure of the role of vocational education can be measured from the balance of these two objectives; there is the development of the whole person and the development of the entire Indonesian society. More specifically, the purpose of vocational education includes four main dimensions: Developing basic human qualities that include the quality of thinking power, emotional intelligence, physical power, to develop the instrumental quality/functional quality, namely the mastery of science, technology, art, and sport, strengthening identity as the nation of Indonesia, and maintaining the survival and development of the world. The following outlined the dimensions of the purpose of vocational education.